China's pawn-broking industry and the puzzle of losses during the global financial crisis in 2008-2009 - Zhou, Liming; Yao, Shujie; Wang, Jinmin; Ou, Jinghua (National University of Singapore, East Asian Institute, 2017)
In China, pawnbrokers not only provide financial intermediation services to individuals and households who need to finance their short-term gap between consumption and income like those in many other countries, but also serve as a supplementary financing channel for private entrepreneurs and small and medium-sized enterprises (SMEs) who face difficulty in obtaining formal credits. This paper uses the first-hand survey data in 2008-2009 in Zhejiang Province, one of the pioneering regions for developing pawn-broking business, to study the special characteristics of the pawn-broking industry and explain why it has become a viable and useful financing instrument in transitional China. Through examining why there was a serious setback and widespread loss in the industry during the global financial crisis in 2008-09, we argue that the crisis increased the default rate of export-oriented SMEs, which reduced their demand for pawn-broking loans. The strict regulations in the pawn-broking industry and the low efficiency of litigation in China also increased the operation costs of handling defaults by the pawnshops, leading to a temporary setback in an otherwise rapidly growing pawnbroking business during the crisis. However, the pawn-broking industry will continue to play an important role in financing SMEs in China in the foreseeable future.